Tundra disturbance studies IV. Species establishment on anthropogenic primary surfaces, Yamal Peninsula, northwest Siberia, Russia - Forbes, B.C. (1997)
Large-scale industrial development in northwest Siberia is resulting in extensive disturbance in a region of low arctic tundra with few data on vegetation responses to such change. Groups of plant species are described for a variety of human-induced surfaces four years after their creation, as well as in adjoining control areas. Ordination and floristic classification reveal active roadsides to be similar to abandoned lowland sand quarries. Constrained ordination indicates a gradient of soil pH, with values being highest in sand quarries and on roadsides. Rorippa palustris and Polygonum humifusum, ruderal species with a pronounced southerly range were among the dominant plants along roadsides and in lowland sand quarries. These are presumed to have migrated north along the road corridor. Floristics in upland primary seres reflected well their proximal natural communities, with 50-90% of the observed colonists present in the adjoining tundra. This was not the case in lowland seres, where colonists originating from the undisturbed vegetation were virtually absent.